2020
DOI: 10.3390/ijms21030934
|View full text |Cite
|
Sign up to set email alerts
|

Ketone Bodies Promote Amyloid-β1–40 Clearance in a Human in Vitro Blood–Brain Barrier Model

Abstract: Alzheimer’s disease (AD) is characterized by the abnormal accumulation of amyloid-β (Aβ) peptides in the brain. The pathological process has not yet been clarified, although dysfunctional transport of Aβ across the blood–brain barrier (BBB) appears to be integral to disease development. At present, no effective therapeutic treatment against AD exists, and the adoption of a ketogenic diet (KD) or ketone body (KB) supplements have been investigated as potential new therapeutic approaches. Despite experimental ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 92 publications
1
40
0
Order By: Relevance
“…βhB is an HDAC inhibitor [ 94 , 95 ], providing a mechanistic basis for βhB-mediated suppression of CypA-NFκB-MMP9 cascade via an increase in the pathway inhibitor, LRP1, which would also support Aβ clearance. Indeed, βhB was recently shown to increase LRP1 levels in a human BBB model [ 91 ]. Furthermore, βhB inhibits the NFκB component of the pathway by binding GPR109A receptor [ 96 , 97 ], which the Montagne group found was sufficient to protect the BBB in ApoE4 mice [ 21 ].…”
Section: Precision Nutrition Considerationsmentioning
confidence: 99%
“…βhB is an HDAC inhibitor [ 94 , 95 ], providing a mechanistic basis for βhB-mediated suppression of CypA-NFκB-MMP9 cascade via an increase in the pathway inhibitor, LRP1, which would also support Aβ clearance. Indeed, βhB was recently shown to increase LRP1 levels in a human BBB model [ 91 ]. Furthermore, βhB inhibits the NFκB component of the pathway by binding GPR109A receptor [ 96 , 97 ], which the Montagne group found was sufficient to protect the BBB in ApoE4 mice [ 21 ].…”
Section: Precision Nutrition Considerationsmentioning
confidence: 99%
“…Other neuroprotective mechanisms that have been highlighted against the development of AD are the reduction of the Amyloid Precursor Protein (APP) production [91] and of Aβ deposition [103]. Moreover, a recent study has shown that in vitro KBs are able to induce Aβ clearance from the brain to blood [127]. According to some evidence, treatment with KD has been also associated with an increase of angiogenesis and capillary density, suggesting that the KBs may support the cognitive processes through an improvement of the cerebral microvascularization [94].…”
Section: Suggested Mechanisms Between Ketogenic Diet and Alzheimer's mentioning
confidence: 99%
“…After 6 days of co-culture, the resulting hBLECs express TJ proteins at cell-cell contacts and transporters typically observed in the brain endothelium, maintaining the properties of in vivo BBB for at least 20 days [28], a period during which we performed transport experiments. This model is now widely used to investigate BBB physiology, as well as molecules and cells passage across the BBB [80][81][82][83][84][85]. The loading of the human BBB model with GM1 or OligoGM1, followed by the measure of permeability parameters, provided evidence to consider OligoGM1 as a molecule transported by the paracellular mechanism, and importantly with a rate 20-fold higher then ganglioside GM1 (Figure 3).…”
Section: Discussionmentioning
confidence: 99%